2020
DOI: 10.1093/icb/icaa089
|View full text |Cite
|
Sign up to set email alerts
|

Convergent Evolution of Cichlid Fish Pharyngeal Jaw Dentitions in Mollusk-Crushing Predators: Comparative X-Ray Computed Tomography of Tooth Sizes, Numbers, and Replacement

Abstract: Synopsis Dental convergence is a hallmark of cichlid fish adaptive radiations. This type of repeated evolution characterizes both the oral jaws of these fishes as well as their pharyngeal jaws that are modified gill arches used to functionally process prey like hard-shelled mollusks. To test several hypotheses regarding the evolution of cichlid crushing pharyngeal dentitions, we used x-ray computed tomography (CT) scans to comparatively examine dental evolution in the pharyngeal jaw of a diversi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
14
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(16 citation statements)
references
References 82 publications
2
14
0
Order By: Relevance
“…and extent of LPJ divergence was comparable to divergence patterns in species pairs in older, more established cichlid radiations (Muschick et al 2012;Kusche et al 2014;Burress 2016;Hulsey et al 2020). We also report the first evidence of niche-specific differences in parasite load, and divergent expression regulation of major adaptive immune response networks between ecomorphs in Lake Masoko (Supplementary Fig.…”
Section: Discussionsupporting
confidence: 69%
“…and extent of LPJ divergence was comparable to divergence patterns in species pairs in older, more established cichlid radiations (Muschick et al 2012;Kusche et al 2014;Burress 2016;Hulsey et al 2020). We also report the first evidence of niche-specific differences in parasite load, and divergent expression regulation of major adaptive immune response networks between ecomorphs in Lake Masoko (Supplementary Fig.…”
Section: Discussionsupporting
confidence: 69%
“…1). We found that the observed direction and extent of LPJ divergence was comparable to divergence patterns in species pairs in older, more established cichlid radiations 34, 35, 37, 41 . We also report the first evidence of niche-specific differences in parasite load, and divergent expression regulation of major adaptive immune response networks between ecomorphs in Lake Masoko (Supplementary Fig.…”
Section: Discussionsupporting
confidence: 57%
“…1i; Supplementary Fig. 2), including body depth, head depth and length, size and position of the pectoral fin (important for manoeuvring [38][39][40] ), and size and position of the mouth (associated with feeding modality 41,42 ).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…More specifically, our data suggest that pelagic foraging "drives" species-and environment-specific DE. This may seem counterintuitive as diets that involve large/hard prey items are generally considered to be the more mechanically demanding compared to small/soft food (Muschick et al, 2011;Gunter et al, 2013;Hulsey et al, 2020). However, Navon et al (2020) showed that in MZ bone matrix was deposited at a fast rate under pelagic foraging conditions, and speculated that suction feeding imposes mechanical load on the feeding apparatus as animals repeatedly open and protrude their jaws.…”
Section: Discussionmentioning
confidence: 99%